2014
DOI: 10.1002/dvdy.24132
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles for hu li tai shao and swallow in cytoskeletal organization during Drosophila oogenesis

Abstract: Background: Cytoskeletal organization is essential for localization of developmentally significant molecules during Drosophila oogenesis. Swallow (Swa) and an isoform of Hu li tai shao (Ovhts-RC) have been implicated in the organization of actin filaments in developing oocytes but their precise roles have been obscured by the dependence of hts RNA localization on swa function. The functional significance of hts RNA localization in the oocyte has not been established. Results: In this study we examine Ovhts-RC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…To test the role of HtsRC independently of Filamin, we examined the formation of F-actin aggregates in cheerio mutant somatic follicle cells overexpressing HtsRC from the tubulin-ovhts-htsN4∆100 transgene. This ovhts construct was previously shown to drive the formation of HtsRC/F-actin structures (Pokrywka et al 2014). We have found the structures formed by this transgene in the somatic follicle cells to be consistent with those generated by other HtsRCexpressing transgenes driven by tubulin-Gal4 ( Figure S3).…”
Section: Filamin Is Important For Htsrc-mediated F-actin Aggregate Fosupporting
confidence: 80%
See 1 more Smart Citation
“…To test the role of HtsRC independently of Filamin, we examined the formation of F-actin aggregates in cheerio mutant somatic follicle cells overexpressing HtsRC from the tubulin-ovhts-htsN4∆100 transgene. This ovhts construct was previously shown to drive the formation of HtsRC/F-actin structures (Pokrywka et al 2014). We have found the structures formed by this transgene in the somatic follicle cells to be consistent with those generated by other HtsRCexpressing transgenes driven by tubulin-Gal4 ( Figure S3).…”
Section: Filamin Is Important For Htsrc-mediated F-actin Aggregate Fosupporting
confidence: 80%
“…Previous work from our lab has shown that the Ovhts polyprotein, which is produced from this mRNA, undergoes post-translational cleavage to produce HtsF, a truncated Adducin protein that localizes to fusomes (magenta, Figure 1B-C), and HtsRC, which localizes to ring canals (green, Figure 1B-C) (Petrella et al 2007). In addition to ring canals, HtsRC is also found on cytoplasmic actin bundles at stage 10B and on the oocyte cortex in later stages (Huelsmann et al 2013;Pokrywka et al 2014). The level of HtsRC in egg chambers is under the control of a Cullin3 RING Ubiquitin ligase (CRL3) in which Kelch is the substrate adaptor that binds HtsRC, leading to poly-ubiquitylation of HtsRC and its destruction by the proteasome (Hudson et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the gene hu li tai shao ( hts ) has been implicated in filament growth at the oocyte cortex and assembling actin at ring canals in developing egg chambers (Yue and Spradling ; Pokrywka et al. ), yet in this study was found to be male‐biased across all tissues.…”
Section: Discussionmentioning
confidence: 60%
“…Second, eight additional candidate genes have been previously implicated in ovary development: hts (Snapp et al 2004; Pokrywka et al 2014), cher (Sokol and Cooley 2003), Mdr49 (Ricardo and Lehmann 2009), tai (Bai et al 2000), pan (Jordan et al 2000), RhoGEF64c (Wang et al 2006), Nlg1 , and VAChT (Soshnev et al 2012). The overlap with genes implicated in ovary development provides additional confidence in the GWAS predictions for these genes.…”
Section: Discussionmentioning
confidence: 99%